2023
DOI: 10.3389/feduc.2023.983349
|View full text |Cite|
|
Sign up to set email alerts
|

An exploratory analysis of divergent patterns in reading progression during a tablet-based literacy program

Abstract: We conducted exploratory research on divergent patterns in reading progression among early grade learners in a low-resourced community to identify key determinants of high versus low reading progress. The sample comprised 30 learners who were purposively selected from participants in a 13-month tablet-based literacy program at a peri-urban Malawi primary school to represent high and low progressing readers. We employed stepwise logistic regression to test the independent contributions of (1) a composite measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Studies evaluating the efficacy of onecourse on learning outcomes have shown significant improvements in early grade literacy and mathematics in Malawi, for mainstream children and children with Special Educational Needs and Disabilities (SEND), as well as the UK (Pitchford, 2015;Hubber et al, 2016;Outhwaite et al, 2017Outhwaite et al, , 2018Pitchford et al, 2018Gulliford et al, 2021;Bardack et al, 2023). Results of these evaluation studies demonstrate consistent and reliable learning gains can be achieved with this education technology regardless of context.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating the efficacy of onecourse on learning outcomes have shown significant improvements in early grade literacy and mathematics in Malawi, for mainstream children and children with Special Educational Needs and Disabilities (SEND), as well as the UK (Pitchford, 2015;Hubber et al, 2016;Outhwaite et al, 2017Outhwaite et al, , 2018Pitchford et al, 2018Gulliford et al, 2021;Bardack et al, 2023). Results of these evaluation studies demonstrate consistent and reliable learning gains can be achieved with this education technology regardless of context.…”
Section: Introductionmentioning
confidence: 99%